POLICY OPTIONS FOR THE ENERGY SECTOR IN MAURITIUS - Philogène, Didier (My University, 2011)
The objectives of this research were to identify the main issues which affect and influence policy decisions in the energy sector in Mauritius. The study aims at providing valuable insights to reinforce the energy sector while supporting economic growth. A qualitative survey using in-depth, semi-structured interviews was used as a research instrument for collecting data. The sample frame consisted of people from four stakeholder groups namely Regulatory Bodies, Experts and Consultants, Independent Power Producers and people from Industries. The findings obtained during the personal interviews were presented in the form of tables for each of the stakeholder groups. Then the content analysis method was used for the interpretation of the data collected. The patterns and trends that emerged were analysed and discussed to answer the research problem and hence used to address the research propositions. The research revealed that the major problems affecting the energy sector are of three folds, namely, economic, environmental and strategic. Various solutions, with regards to these three sectors have been proposed by the respondents to address the main issues influencing the energy sector. It has been surprising to note that no major differences in the opinions expressed by the respondents among the different stakeholder groups were observed. In fact, they have more or less identified the same problems in the Energy Sector in Mauritius and the suggestions proposed were oriented towards the same objectives
MBA - WBS
Keywords: Energy sector, Mauritius